PENGABDIAN KEPADA MASYARAKAT DALAM BIDANG PENDIDIKAN MELALUI KULIAH KERJA NYATA (KKN) DI DESA PEKAN GUNUNG MERIAH - Maya Firanti, Ela; Br. Ginting, Rani Safitri; Mawaddah, Dhea Wafiq; Fadhilah, Rizki; Putri, Aulia; Harahap, Yulia Sari; Amin, Teguh Satria (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
As part of the Tri Dharma of Higher Education, students are required to help the community. KKN in this village starts from July to August. Students received a number of mandates from the Muslim Nusantara Al Washliyah University (UMNAW) Campus. This is intended to support educational improvement. This activity was carried out through observation and field research. Our team has designed several educational activity programs after discussing with KKN students. These programs include:1) Helping students from grade 1 to grade 6 in elementary school in reading, arithmetic and Indonesian language lessons; 2) Providing assistance and collaborating in the teaching process in elementary schools (SD).